IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN MATEMATIKA DI SMK NEGERI 1 GUNUNGSITOLI UTARA - TELAUMBANUA, RESTI JULIANA; MENDROFA, RATNA NATALIA; TELAUMBANUA, YAKIN NIAT; MENDROFA, NETTI KARIANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research is based on the results of preliminary study observations that have been carried out by researchers at the Vocational High School (SMK) Negeri 1 Gunungsitoli Utara which is located on Jl. Tafaeri Menuju Desa Hambawa, Gunungsitoli City. Where it turns out that SMK Negeri 1 Gunungsitoli Utara has used the Independent Curriculum in the 2023/2024 academic year so that the purpose of this study is